The meaning of the Dead Sea scrolls their significance for understanding the Bible, Judaism, Jesus, and Christianity - VanderKam, James C. 1946- (HarperSanFrancisco, 2002)
Drawing together all the evidence, this timely book explores: The discovery and dating of the Dead Sea Scrolls; their relationship to the Hebrew Bible, Apocrypha, and New Testament; their messianic and apocalyptic messages; the identity, nature, and theology of the Qumran community; the nonbiblical scrolls; and controversies surrounding the scrolls. This comprehensive, guide provides an introduction to all aspects of the scrolls, including their teachings, the community that created them, the world of Judaism, the origins of Christianity, and our understanding of Jesus and the New Testament. Features photos of the original texts, the sites, and the scholars who deciphered them, and includes illustrative passages from the scrolls.
Includes bibliographical references and indexes
Keywords: Bible. -- O.T. -- Criticism, interpretation, etc; Dead Sea scrolls; Dead Sea scrolls -- Relation to the New Testament; Qumrantexte; Qumran community